2001
DOI: 10.1540/jsmr.37.67
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Impairment of Endothelium-Dependent Relaxation of Arteries from Spontaneously Hypertensive and L-NAME-Treated Wistar Rats.

Abstract: Effects of chronic treatment of normotensive Wistar rats with N(omega)-nitro-L-arginine methyl ester (L-NAME) on blood pressure and on endothelium-dependent relaxation of the aorta, carotid and iliac arteries were studied. The endothelium-dependent relaxation was compared in arteries from normotensive Wistar Kyoto rats (WKY) and genetically hypertensive rats (stroke-prone spontaneously hypertensive rats, SHRSP). Chronic treatment of normotensive Wistar rats with L-NAME caused an elevation of blood pressure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
6
11
0
1
Order By: Relevance
“…Chronic administration of L-NAME caused an elevation of blood pressure in Wistar rats as previously reported (Arnal et al, 1992 andBaylis et al, 1992;Ribeiro et al, 1992;Bryant et al, 1995;Küng et al, 1995;Dowell et al, 1996;Takase et al, 1996;Henrion et al, 1997;Ledingham and Laverty, 1997;Moreau et al, 1998;Zhao et al, 1999;Sekiguchi et al, 2001). In the present study, we showed that while chronic treatment of Wistar rats with L-NAME elevated SBP, the pulmonary arterial blood pressure was unchanged.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Chronic administration of L-NAME caused an elevation of blood pressure in Wistar rats as previously reported (Arnal et al, 1992 andBaylis et al, 1992;Ribeiro et al, 1992;Bryant et al, 1995;Küng et al, 1995;Dowell et al, 1996;Takase et al, 1996;Henrion et al, 1997;Ledingham and Laverty, 1997;Moreau et al, 1998;Zhao et al, 1999;Sekiguchi et al, 2001). In the present study, we showed that while chronic treatment of Wistar rats with L-NAME elevated SBP, the pulmonary arterial blood pressure was unchanged.…”
Section: Discussionsupporting
confidence: 89%
“…L-NAME has been shown to inhibit the synthesis of NO in the endothelium (Rees et al, 1990;Pfeiffer et al, 1996), and such inhibition has been reported to enhance vascular smooth muscle contraction (Martin et al, 1986;Alosachie and Godfraind, 1988;Osugi et al, 1990;Kaneko and Sunano, 1993). We have also observed that EDR of the aorta and of the carotid and iliac arteries from L-NAME-treated rats was impaired (Sekiguchi et al, 2001). This impairment of EDR in arteries of L-NAME-treated rats is thought to be mainly due to inhibition of NO production by the drug (Arnal et al, 1992;Baylis et al, 1992;Ribeiro et al, 1992).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations